The Effects of Entrepreneurial Orientation, Social Media, and Managerial Ties on Msme Performance in Surabaya City - Mediany Kriseka Putri; Dimas Rizqie Zanetti (Journal of Management Economic and Financial, 2024)
The study investigates the role of entrepreneurial orientation, social media usage, and managerial ties in the performance of MSMEs in Surabaya City. MSMEs are vital for economic growth and job creation but often face challenges such as limited resources and technological adoption. The research aims to understand how entrepreneurial orientation impacts MSME performance directly and through social media usage and managerial ties. A quantitative approach was employed, using surveys to collect data from MSMEs in Surabaya, and statistical analysis was conducted to test the relationships between the variables. The findings indicate that entrepreneurial orientation does not directly enhance firm performance but significantly influences social media usage and managerial ties, both of which positively affect firm performance. Specifically, social media usage improves customer interaction and marketing, while strong managerial ties provide access to valuable resources. The study highlights the importance of leveraging social media and managerial relationships to improve MSME performance, suggesting that policymakers and business owners should focus on enhancing these areas to support MSME growth and sustainability. Further research is recommended to explore additional factors such as government support and funding access to provide deeper insights into SME performance dynamics.